2013
DOI: 10.1371/journal.pcbi.1003139
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Stochastic Dynamics Enable Robust Cell Polarization

Abstract: Although cell polarity is an essential feature of living cells, it is far from being well-understood. Using a combination of computational modeling and biological experiments we closely examine an important prototype of cell polarity: the pheromone-induced formation of the yeast polarisome. Focusing on the role of noise and spatial heterogeneity, we develop and investigate two mechanistic spatial models of polarisome formation, one deterministic and the other stochastic, and compare the contrasting predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 50 publications
(61 reference statements)
2
71
0
Order By: Relevance
“…Two-color imaging revealed that all of these markers concentrated in the vicinity of the polarity patch (Fig. 1D), but Spa2 and Sec4 formed a tighter cluster than Bem1, as previously noted (Lawson et al, 2013). In contrast, Abp1-marked endocytosis sites were clustered in a broader zone surrounding the tight Sec4 patch.…”
Section: Resultssupporting
confidence: 83%
“…Two-color imaging revealed that all of these markers concentrated in the vicinity of the polarity patch (Fig. 1D), but Spa2 and Sec4 formed a tighter cluster than Bem1, as previously noted (Lawson et al, 2013). In contrast, Abp1-marked endocytosis sites were clustered in a broader zone surrounding the tight Sec4 patch.…”
Section: Resultssupporting
confidence: 83%
“…We assume that the initial concentrations of mRNA and the target protein are zero, and use spatial stochastic simulation to investigate the gene expression pattern, a model that has been widely used and verified by both theoretical [3639] and experimental [39, 40] observations. To account for crowding, we developed a modified next subvolume method (NSM) to approximately solve the reaction-diffusion master equation (RDME) [41] capable of explicitly treating the crowding agent amount, distribution, and interactions (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The typical large concentration of proteins in cells permits the use of deterministic dynamics, however, the concentration of enzymes is smaller and stochastic effects may become relevant. The use of a stochastic model may enhance domain formation [34,35].…”
Section: Discussionmentioning
confidence: 99%